Meningkatkan Kinerja Dengan Menyelaraskan Kepemimpinan Dan Budaya Organisasi - Asmawiyah; Mukhtar, Afiah (STIM-LPI Makassar, 2024)
This research aims to analyze the influence of leadership and organizational culture on employee performance. Effective leadership and a strong organizational culture are recognized as key factors in shaping and improving employee performance. The research method used is a quantitative method with a descriptive and verification approach. The sample in this study was 50 respondents. The data collection technique was carried out through distributing questionnaires. The research results show that leadership and organizational culture have a positive and significant influence on employee performance, both partially and simultaneously.